2016
DOI: 10.1002/oby.21647
|View full text |Cite
|
Sign up to set email alerts
|

High‐fat diet‐induced downregulation of anorexic leukemia inhibitory factor in the brain stem

Abstract: HFD-induced downregulation of anorexic LIF in the brain stem may provide a permissive condition for HFD overconsumption. This may be at least partially mediated by the NTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…There were no changes in the expression of transcript encoding for NPY and POMC (data not shown). The immunoneutralization of LIF in the hypothalamus resulted in reduced STAT3 Tyr705 phosphorylation in the hypothalamus but not in the hippocampus [ 14 ] (Additional file 1 : Figure S2), suggesting that the method was appropriate for a site-specific action of the antibody.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…There were no changes in the expression of transcript encoding for NPY and POMC (data not shown). The immunoneutralization of LIF in the hypothalamus resulted in reduced STAT3 Tyr705 phosphorylation in the hypothalamus but not in the hippocampus [ 14 ] (Additional file 1 : Figure S2), suggesting that the method was appropriate for a site-specific action of the antibody.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…High fat diet (HFD)-induced obesity in rodents is associated with hypothalamic inflammation, a pathological state that is a key characteristic of the disease. In rodents, LIF is downregulated in both the nucleus tractus solitarus of the brainstem and hypothalamus in response to HFD [83,84]. Importantly, LIF can act upon LIF receptors on POMC neurons in an anorexigenic manner by stimulating the release of alpha MSH [85].…”
Section: Leukaemia Inhibitory Factormentioning
confidence: 99%
“…Importantly, LIF can act upon LIF receptors on POMC neurons in an anorexigenic manner by stimulating the release of alpha MSH [85]. Both central and peripheral administration of LIF in rodents reduces body weight [84,86,87].…”
Section: Leukaemia Inhibitory Factormentioning
confidence: 99%
“…It was observed that hypothalamic inhibition of this factor in obesity-resistant mice switched them into the obesity-prone phenotype, which indicates that this adipokine is an obesity-protectant [ 221 ]. On the other hand, a high-fat diet decreased the LIF gene transcription in the brain stems of rats which may contribute to permissive overconsumption and the development of diet-induced obesity [ 93 ]. Moreover, it plays a role in the pathology of various diseases including cancers [ 222 ].…”
Section: Interleukinsmentioning
confidence: 99%